Optimising Regional Financial Performance through Capital Expenditure and Regional Revenue in Bengkalis Regency 2017-2020 - Syahrial Abdi; Bahrullah Akbar; Dedeh Maryani; Marja Sinurat (ARISTO, 2023)
Local Government Governance in Improving Regional Financial Performance on the Analysis of Capital Expenditure and Regional Revenue from 20017 to 2020 proves that the Quality and Allocation of Expenditure has not been seen due to the Pattern of Leadership Culture and Geopolitics of Bengkalis Regency. Capital Expenditure has not been prepared to build infrastructures related to the community’s economic growth, which will ultimately impact increasing Regional Original Revenue (PAD). This research is a qualitative descriptive type, intending to know the work of regional finance; there are 5 (five) elements, namely: 1) Degree of Decentralisation; 2) Financial Dependence on the Central Government; 3) Financial Independence; 4) Effectiveness of local revenue; 5) Degree of BUMD Contribution. This paper proves that optimal and effective capital expenditure and the ability to develop an integrated revenue-raising program can improve regional financial performance.